Personalized Learning-based Segmentation of Thoracic Aorta and Main Branches for Diagnosis and Treatment Planning - Vitanovski, Dime; Ralovich, Kristof; Ionasec, Razvan; Zheng, Yefeng; Suehling, Michael; Krawtschuk, Waldemar; Hornegger, Joachim; Comaniciu, Dorin (Cardiac and Vascular Imaging, 2012)
Coarctation of the aorta (CoA), is an obstruction of the aortic arch present in 5-8% of congenital heart diseases. For children older than a year, CoA is increasingly treated by aortic stenting instead of surgical repair. In pediatric cardiology, CMR is accepted as the standard non-invasive imaging modality to assess the aortic arch in it's entire spatial context [1]. Interpreting such 3D datasets are required to assess the underlying anatomy during both diagnosis and therapy planning phases. However this process is time consuming and varies with operator skills. Within this study we propose for the first time in our knowledge a method of automatic segmentation of the lumen of thoracic aorta and main branches. The personalized model of the aorta and the supra-aortic arteries, automatically estimated from 3D CMR data, will provide better understanding of the complexity of pathology and assist the cardiologist to choose the best treatment and timing of repair. A hierarchical framework based on robust machine-learning algorithms is proposed to estimate the personalized model parameters. Experiments throughout 212 3D CMR volumes demonstrate model estimation error of 3.24 mm and average computation time of 8 sec. combined with clinical evaluation on 32 patients. © 2012 IEEE.
UnivIS-Import:2017-03-24:Pub.2012.tech.IMMD.IMMD5.person